1957
DOI: 10.1039/jr9570001946
|View full text |Cite
|
Sign up to set email alerts
|

374. Lactones. Part V. Experiments relating to mycophenolic acid

Abstract: The structure of mycophenolic acid has been confirmed as (I) by infrared spectroscopy and by the synthesis of the degradation product, 6-carboxymethyl-6 : 7-dimethoxy-4-methylphthalide (X ; R = CH2*C02H) .FROM degradative studies by Raistrick and his co-workers 1-4 the structure of mycophenolic acid, a metabolic product of strains of Penicillium brevi-compactum, is almost certainly structure (I). Birkinshaw, Raistrick, and ROSS,, however, admitted slight doubts as to which of the two nuclear hydroxyl groups in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1970
1970
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…To compare the inhibitory e †ect of aspyrone (1) with the biological activity of aspyrone derivatives (3,4,5), asperlactone (2) and captan, a known fungicide, Ðve moulds were tested ( Table 2). The aspyrone derivatives with a modiÐcation only in the hydroxyl group (3,4) retained activity against Fusarium oxysporum and Colletotrichum coccodes, but this disappeared when the epoxy group was removed (5). Asperlactone (2) also showed no activity against the two fungi.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To compare the inhibitory e †ect of aspyrone (1) with the biological activity of aspyrone derivatives (3,4,5), asperlactone (2) and captan, a known fungicide, Ðve moulds were tested ( Table 2). The aspyrone derivatives with a modiÐcation only in the hydroxyl group (3,4) retained activity against Fusarium oxysporum and Colletotrichum coccodes, but this disappeared when the epoxy group was removed (5). Asperlactone (2) also showed no activity against the two fungi.…”
Section: Resultsmentioning
confidence: 99%
“…To compare the antibiotic e †ect of aspyrone (1) with the biological activity of aspyrone derivatives, asperlactone (2) and terramicin, a known antibiotic, four bacteria and one yeast were tested. Table 4 shows that, in general, aspyrone (1) showed better activity than asperlactone (2) or aspyrone derivatives (3,4,5), although terramicin always showed the best activity against all bacteria. Some of these results, mainly the activity against E. coli and S. aureus, could be explained in terms of product solubility or by supposing the bioactive compound was not directly the lactone group but a product resulting from opening the ring.…”
Section: Tablementioning
confidence: 98%
See 2 more Smart Citations
“…Recently, two groups of researchers (5, 6) reported on the antitumor activity of mycophenolic acid, while Williams et al (7) reported that the substance exhibited both antiviral and antitumor properties. Work has been done, both chemical and physical in nature, to elucidate the structure of mycophenolic acid (8,9 ) and some related compounds, which were isolated from the culture filtrates of a strain that produces mycophenolic acid (10). Birch and Wright (11) have devised a scheme for the total synthesis of mycophenolic acid.…”
mentioning
confidence: 99%